Use of surfactant in neonatal intensive care units - M Sholeh Kosim (Indonesian Pediatric Society Publishing House, 2016)
Surfactant is currently an important therapy for newborns in neonatal intensive care units (NICUs) with respiratory problems, specifically respiratory distress syndrome (RDS). Surfactant was initially used in 1959, after it was recognized for maintaining lung inflation at low transpulmonary pressures. Avery and Mead in Jobe reported that saline extracts from the lungs of preterm infants with RDS lacked the low surface tension characteristics of pulmonary surfactant. Subsequently, in 1980, clinical potential of surfactant therapy for RDS was demonstrated by Fujiwara et al, reported in Jobe, in the use of surfactant prepared from an organic solvent extracted from bovine lung (Surfactant TA). Small randomized controlled trials (RCTs) in 1985, which tested surfactants prepared from bovine alveolar-lavage or human amniotic fluid, demonstrated significant decrease in pneumothorax and death rates. Subsequent multi-center trials demonstrated decreased death rates and complications of RDS; although still investigational, its use begun in 1989. A synthetic surfactant was approved for the treatment of the syndrome in the United States in 1990, and an animal surfactant was approved in 1991. These surfactants represent a new class of drug developed specifically for preterm infants.